Dinamika Kajian Sanad Hadis Kaum Orientalis : Dynamics of Orientalist Sanad Hadith Studies - Sofyan Nur (JAWAMI'UL KALIM: Jurnal Kajian Hadis, 2025)
This research is an effort to read orientalist studies on one of the sources of Islamic law, namely al-Hadith, especially on one of the main instruments that make up hadith, namely sanad. The Orientalist movement views the sanad as an important object of study because by studying it they can design their version of the hadith structure which aims to undermine the authenticity of the hadith itself and its validity as a source of Islamic law. The research method used is descriptive qualitative with a historical approach, by searching references to the works of scholars. The results of this research show that orientalists from time to time have given birth to various theories and spread various doubts regarding hadith sanads which fundamentally reject the authenticity of hadiths because they are built on sanads which are all false. This research can be a door to examine more deeply each theory and its influence.